2023
DOI: 10.1002/adma.202211103
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Nano‐Islands (SANIs): A Robust Atomic–Nano System for Versatile Heterogeneous Catalysis Applications

Abstract: and conventional transition metals SACs supported on metal or non-metal carriers) have been developed and upgraded greatly. [3][4][5] Theoretically speaking, the dispersion limit of supported metal catalysts is the uniform distribution of the metal in the form of single atoms on the support: this is not only the ideal state of supported metal catalysts, but also brings the science of catalysis from the "nano age" into the "atomic age". [6][7][8] SACs usually refer to the active sites where isolated metal atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Utilizing nanostructured support materials with high surface area makes ALD an ideal tool to explore energy applications. 90,91…”
Section: Precise Control At the Interface Using Aldmentioning
confidence: 99%
“…Utilizing nanostructured support materials with high surface area makes ALD an ideal tool to explore energy applications. 90,91…”
Section: Precise Control At the Interface Using Aldmentioning
confidence: 99%
“…For the control of the surface atomic composition of the catalysts, doping a heterometal atom on the surface is a well-known strategy. 31–43 This induces the formation of a reactive center, i.e. , a multi-element ensemble site, for facilitating the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth is prone to agglomerate at high temperatures, resulting in insufficient active sites . Accordingly, to promote the catalytic activities, a superior approach is required to design single-atom (SA) bismuth catalysts. However, only a few studies have been reported to investigate the catalytic performance of Bi single atoms and the associated mechanisms. , Up to date, there are yet to be any studies on the photocatalytic performance of Bi single atoms as a cocatalyst in semiconductors. Bi single-atom-based materials are typically synthesized via high-temperature pyrolysis (up to 900 or 1000 °C), , which is energy-intensive and requires harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%